Một số vấn đề về xác định cha, mẹ và con ngoài giá thú theo Luật hôn nhân và gia đình Việt Nam - Nguyễn Văn Cừ (2002)
Bàn về vấn đề về xác định cha, mẹ và con ngoài giá thú theo Luật hôn nhân và gia đình Việt Nam